The 1st Baltic Osseointegration Academy and Lithuanian University of Health Sciences Consensus Conference 2016. Summary and Consensus Statements: Group II - Peri-Implantitis Diagnostics and Decision Tree - Tolga Fikret Tözüm; Erhan Dursun; Gintaras Juodzbalys; Jesús López-Martínez; Miguel Padial-Molina; Pablo Galindo-Moreno; Ausra Ramanauskaite; Francisco O'Valle (eJournal of Oral Maxillofacial Research)
Introduction: The task of Group 2 was to review and update the existing data concerning clinical and genetic methods of diagnostics of peri-implantitis. Special interest was paid to the peri-implant crevicular fluid (PICF) overview including analysis of enzymes and biomarkers and microbial profiles from implants.